RELEVANCE OF ENTREPRENEURIAL QUOTIENT IN DETERMINATION OF FUTURE ENTREPRENEURS - S. B. Seshadri, Krishna Kumar Thakur, Dr. Biju Mani Das (International Journal of Modern Agriculture, 2021)
Any quotient explores the degree of specified quality or characteristics. The present era is surging ahead for entrepreneurial work culture, which is working on innovative and creative aspects of human genius towards economic growth and development. The economic growth depends on the entrepreneurial activity of the nation. All developed nations had done good progress on the entrepreneurial encouragement. The quotient like Intelligence quotient, Emotional quotient can predict with reliability, validity and help the researchers to find the interventions. The entrepreneurial quotient if it can be predicted with certainty would help the society to identify the entrepreneurial mindset and competencies to harness through interventions like entrepreneurship Development Programmes and eventually move towards economic growth and development of the nation. This research paper intends to explore the determinants for assessing the future entrepreneurs through entrepreneurial quotient (En.Q).